Literature Review: Peran Pengelolaan Kelas dalam Menciptakan Lingkungan Belajar yang Kondusif - Nadila Amri; Pajarni Pajarni; Sari Wahyuni; Miftahir Rizka; Layyana Syarifah Pane (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
As an important condition for successful learning, strategic classroom management contributes to the creation of a conducive learning environment. The purpose of this study is to examine how classroom management and a conducive learning environment are interrelated and how both contribute to improving teaching standards in the classroom. A literature review is the process used, which involves examining various sources, including books, scientific publications, and previous research findings relevant to the subject. The research findings show that classroom management includes social interaction, behavior control, and the emotional atmosphere of the classroom, in addition to its physical components. To foster a supportive and effective learning environment, teachers play the roles of educators, instructors, mentors, coaches, advisors, innovators, and role models. Effective classroom management creates a supportive learning atmosphere where students feel safe, comfortable, and inspired to engage fully. The success of this management is also influenced by elements such as organizational structure, social-emotional connections, and physical conditions of the classroom. Therefore, the mutually beneficial relationship between classroom management and a supportive learning environment is an important foundation for improving learning standards and successfully achieving educational goals.